Effectiveness of Arabic Debate Community to Improve Students' Arabic Speaking Skills /Efektivitas Komunitas Debat Bahasa Arab Untuk Meningkatkan Kemampuan Berbicara Bahasa Arab Mahasiswa - Abdilah, Azis Aji; Holilulloh, Andi (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2022)
Mahārah al-kalām or speaking skills is a skill that is difficult to master because it does not require language skills only, but language practice and environment are also needed. The use of the debate method as a means to improve students' Arabic speaking skills can also indirectly create a language environment that is very influential for foreign language students. This study aims to determine the effectiveness of the use of the debate method in improving Arabic speaking skills. This research is field research with a descriptive qualitative approach, the data collecting technique is in the form of a note-taking method, the data that has been obtained is analyzed using the intralingual equivalent method. The result of this study is a significant increase in Arabic speaking ability in general as much as 61.5%. When viewed from the aspect of speaking skills there was an increase in the pronunciation aspect as much as 84%. In the vocabulary aspect, the percentage increase reached 87%. In the grammatical aspect, the percentage increase reached 74%, in the fluency aspect the percentage improvement reached 82%, and in the comprehension aspect, the percentage increase in debate among PBA students reached 75%. In the post-test assessment of the PBA student debate community, the highest averages of the five aspects above were pronunciation and fluency.